Edukasi Kesehatan untuk Hidup Sehat Bebas Diabetes Melitus - Nabila, Anna; Rahayu, Hesti; Mazaya, Hasna; Saharawati, Regita; Afiati, Farida; Chairani, Aulia Nasywa (Yayasan Daarul Huda Kruengmane, 2025)
Diabetes mellitus is a non-communicable disease characterized by elevated blood glucose levels due to impaired insulin production or function. This condition poses a serious public health issue because it can lead to long-term complications such as kidney failure, vision problems, nerve damage, and heart disease. The lack of public awareness about risk factors, symptoms, and the importance of early detection contributes to the rising number of diabetes cases in Indonesia. This community service activity aimed to increase public knowledge about diabetes mellitus through health education and diabetes foot exercise. The event was held on Saturday, May 17, 2025, in Gang Guntur, Cimanggis, Depok, targeting adults and the elderly. The implementation methods included interactive lectures, Q&A sessions, random blood sugar tests (GDS), and a practical diabetes foot exercise session. There were 18 participants who attended the event. This program is expected to improve participants’ understanding of how to prevent and manage diabetes independently in their daily live. Moreover, it aims to raise awareness of the importance of a healthy lifestyle as a promotive and preventive measure against diabetes mellitus.